Andriievska V. M. Thanatological motives in the Arthur Schnitzler’s short stories - Andriievska V. M. (Philological Treatises, 2020)
Reflection of thanatological motives in the Arthur Schnitzler’s short stories – modern impressionistic Austrian author, - was explored in the article. The influence of modernistic literary trend and Decadent movement on the author’s works was researched in this article as well as ways of formation and literary development of death’s image within the peculiarities of literary age.